Metabolic control of ovarian function through the sympathetic nervous system: role of leptin - Camila Astudillo-Guerrero; Alfonso H. Paredes; Jorge Escobar; Daniela Fernandois; Rafael Barra; Gonzalo Cruz (Frontiers in Endocrinology)
The link between metabolism and reproduction is well-known. Both undernutrition and obesity affect the reproductive system. Metabolic status influences reproductive physiology by regulating gonadotropin secretion and affecting reproductive organs through hormonal signals. On the other hand, the autonomic nervous system controls follicle development and ovulation in the female reproductive system. This system is regulated by hypothalamic areas associated with metabolism as the Arcuate nuclei (ARC) and paraventricular nuclei (PVN). Metabolic signals, such as nutrients and hormones, acting on the hypothalamus may play a crucial role in modulating sympathetic innervation of the ovary and other reproductive organs. Some of these hormones are leptin, insulin, and GLP-1 that act directly in the hypothalamus to activate the sympathetic nervous system. In this minireview, we propose that leptin could be an important regulator of sympathetic innervation in reproductive tissues. Leptin may affect the density or activity of sympathetic nerves, thereby affecting reproductive function. We also speculate that other hormones such as insulin and GLP-1 may activate sympathetic nerves to the ovary. Additionally, we explore how early-onset obesity can cause lasting changes in the autonomic control of metabolic and reproductive organs, especially in the ovary. This suggests that the hyperactivation of sympathetic nerves in adulthood, due to metabolic programming, could be a possible cause of reproductive and metabolic disorders, such as polycystic ovary syndrome.